Non-Destructive Structural Assay Using X-Ray Micro-Tomography to Estimate Mass Density Differences in Rabbit Bone Samples - Pérez, P. (2016)
Fil: Pérez, P. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.